2014
DOI: 10.1021/jm401752p
|View full text |Cite
|
Sign up to set email alerts
|

4-(3-Chloro-5-(trifluoromethyl)pyridin-2-yl)-N-(4-methoxypyridin-2-yl)piperazine-1-carbothioamide (ML267), a Potent Inhibitor of Bacterial Phosphopantetheinyl Transferase That Attenuates Secondary Metabolism and Thwarts Bacterial Growth

Abstract: 4′-Phosphopantetheinyl transferases (PPTases) catalyze a post-translational modification essential to bacterial cell viability and virulence. We present the discovery and medicinal chemistry optimization of 2-pyridinyl-N-(4-aryl)piperazine-1-carbothioamides, which exhibit submicromolar inhibition of bacterial Sfp-PPTase with no activity toward the human orthologue. Moreover, compounds within this class possess antibacterial activity in the absence of a rapid cytotoxic response in human cells. An advanced analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 64 publications
(133 reference statements)
1
44
0
Order By: Relevance
“…Inhibitors of the PPTase enzyme will prevent the attachment of the TAMRA-CoA to the peptide, preventing the FRET signal [28, 29]. A subsequent high throughput screen of over 300,000 compounds yielded the identification of ML267 (Figure 4B) as an inhibitor of Sfp-PPTase, with approximately 30-fold selectivity over the bacterial fatty acid synthesis PPTase and greater than 500-fold relative to the human orthologue [31, 32]. ML267 is an allosteric, reversible inhibitor with a high nanomolar IC 50 value 3 that is bactericidal against Gram positive pathogens including B. subtilis and methicillin-sensitive and -resistant strains of Staphylococcus aureus (MRSA).…”
Section: Inhibitors Of Nrps Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitors of the PPTase enzyme will prevent the attachment of the TAMRA-CoA to the peptide, preventing the FRET signal [28, 29]. A subsequent high throughput screen of over 300,000 compounds yielded the identification of ML267 (Figure 4B) as an inhibitor of Sfp-PPTase, with approximately 30-fold selectivity over the bacterial fatty acid synthesis PPTase and greater than 500-fold relative to the human orthologue [31, 32]. ML267 is an allosteric, reversible inhibitor with a high nanomolar IC 50 value 3 that is bactericidal against Gram positive pathogens including B. subtilis and methicillin-sensitive and -resistant strains of Staphylococcus aureus (MRSA).…”
Section: Inhibitors Of Nrps Biosynthesismentioning
confidence: 99%
“…B. ML267 inhibitor of Sfp-PPTase identified by high throughput screening using the FRET assay using probes in part A. [31, 32] C. BODIPY-TMR fluorescence polarization probe developed to assay PPTase inhibitors. [33] D. The two most inhibitory compounds of the PPTase from M. tuberculosis are shown, determined when using the fluorescence polarization assay where the probe is the FRET acceptor in part A.…”
Section: Figurementioning
confidence: 99%
“…To rule out the possibility that any PPTase was missed in this analysis, we used 2-pyridinyl- N -(4-aryl)-piperazine-1-carbothioamides (4–6), specific inhibitors of bacterial Sfp-like PPTases (Foley et al, 2014), to shut off legioliulin production. Legioliulin production and growth are closely linked.…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme was able to activate the NRPS IndC from P. luminescens , even though no NRPS product is known for any Legionella strain so far confirming this function. To investigate the effect on suppression of the Sfp-type PPTase, we grew L. parisiensis in the presence of Sfp-type PPTase inhibitors (Foley et al, 2014) and showed that legioliulin production, in addition to cell viability, is halted (Table S4; Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation